2020
DOI: 10.1088/1755-1315/471/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of biogas production from pineapple waste by acid-alkaline pretreatment

Abstract: The present study examined the effect of acid-alkaline pretreatment on pineapple waste for the performance on the anaerobic digestion. The acid-alkaline pretreatment was carried out by varying pH values from 2 to 12 using HCl and NaOH, and the mixtures were agitated at 250 rpm with the contact time of 24 hrs. The overall result showed that SCOD concentrations increased when pH values were increased. The value of biodegradability of raw waste was about 0.304. The BOD/COD ratios increased to 0.439 and 0.473 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The characterization processes that were carried out on the substrates utilized in the tests are listed in Table 2. The pineapple waste used in this experiment displays a high moisture content that is similar to the pineapple waste that was used by Wichitsathian et al [16] in their study. Furthermore, it is clear that the VS of the pineapple waste used in this study is a little higher.…”
Section: Samples Characterizationmentioning
confidence: 72%
See 2 more Smart Citations
“…The characterization processes that were carried out on the substrates utilized in the tests are listed in Table 2. The pineapple waste used in this experiment displays a high moisture content that is similar to the pineapple waste that was used by Wichitsathian et al [16] in their study. Furthermore, it is clear that the VS of the pineapple waste used in this study is a little higher.…”
Section: Samples Characterizationmentioning
confidence: 72%
“…Apart from being rich in organic matter, pineapple waste also contains a large amount of natural carbohydrates, with cellulose making up the majority (41.8%), followed by lignin (13.2%) and hemicellulose (35.2%). The lignin content in this study is low compared to the literatures [8,16]. Since lignin is resistant to microbial attack and hard to break down, substrates with lower lignin percentages are preferred as a digestion substrate.…”
Section: Samples Characterizationmentioning
confidence: 76%
See 1 more Smart Citation
“…However, Dahunsi et al [181] reported that alkaline pretreatment using sodium hydroxide could increase the gas production of pineapple peels and poultry manure by 91% compared to acid pretreatment. Wichitsathian et al [182] also reported that pineapple waste's specific gas production rate increased from 132.05 L/kg of VS to 866.75 L/kg of VS after pretreatment was applied. For instance, the study by Aworanti et al [183] on the methane potential from the co-digestion of pineapple peels and manures and the optimisation of process parameters such as temperature, solid content and substrate to inoculum ratio discovered that by operating the co-digestion process at 55.2 • C, 6.25% solid content and 1:2 substrate to inoculum ratio could produce a high biogas yield with 71.10% methane content.…”
Section: Biogasmentioning
confidence: 98%
“…Moreover, using these wastes would be a great opportunity to create new products while reducing the amount of waste generated by pineapple canning industrial waste [ 26 ]. The pineapple canning industrial waste was also used for the production of biogas [ 27 ], ethanol [ 28 ], lactic acid [ 29 ], vanillin and vanillic acid [ 30 ], and polyhydroxybutyrate. The use of pineapple industrial wastes such as peel, crown, and its mixture with the core has been studied for BC production [ [31] , [32] , [33] ].…”
Section: Introductionmentioning
confidence: 99%